Testing for partial agonism of the aryl hydrocarbon receptor - Wall, Richard J. (2008)
2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) is the most potent of a group of persistent organic pollutants (POPs). The aryl hydrocarbon receptor (AhR) has a high affinity for these dioxin-like compounds with activation increasing transcription of CYP1A1. The aim of this paper was to measure the agonistic and potential antagonistic effects of four of the most prevalent and potent dioxin-like agonists: 3-Methylcholanthrene (3-MC), 2,3,7,8-Tetrachlorodibenzofuran (TCDF), 2,3,4,7,8-Pentachlorodibenzofuran (PeCDF) and 3,3’,4,4‘,5-Pentachlorobiphenyl (PCB 126), comparing them with TCDD. An example of a suspected partial agonist (DF 203) and an antagonist (CH 233191) were also assayed. A method of measurement that uses real-time PCR was calibrated to quantify the induction of CYP1A1. Potency determination for different incubation times was also investigated using 3-MC and TCDD. An increase in EC50 (~40 fold) between 4 and 24 hours was observed for 3-MC, whereas a lesser difference (~4-fold) was seen with TCDD. This showed that time is a clear variable when measuring CYP1A1 induction. Four individual determinations of the potency of TCDD at inducing P4501A1 gave an average EC50 = 35 pM (± 5.8 pM), demonstrating the reproducibility and reliability of the method. Successful measurement of the agonistic properties of the four compounds was characterised: 3-MC EC50= 2.3 nM (Confidence interval = 1.3 - 3.8 nM); TCDF = 5.8 nM (2.8 - 11 nM); PeCDF = 2.2 nM (1.4 - 3.4 nM); PCB 126 = 765 pM (645 - 907 pM). However, no antagonistic properties were observed demonstrating that within a TCDD containing mixture, they will have no effect on the prediction of TCDDlike toxicity. Nevertheless, the method successfully characterized antagonism in the positive control compounds, DF 203 and CH 223191.